A Multi-hazard Risk Assessment of Buildings in Padang City. (2015) - Mulyani, Rini; Ahmadi, Raudhah; Pilakoutas, Kypros; Hajirasouliha, Iman; Taufik,
Abstract: The main purpose of an earthquake risk assessment is to assess the potential loss of buildings in earthquake prone regions and to provide enough information to employ suitable mitigation strategies. The Mw 9.1 great Sumatra earthquake in 2004 and the Mw 9.0 Japan earthquake in 2011 have highlighted the importance of a multi-hazard risk assessment framework that includes the effects of both earthquake and its associated hazards such as tsunami. The multi-hazard risk assessment of buildings requires several stages including earthquake and tsunami hazard analyses, the vulnerability analysis of buildings, building inventory as well as the risk estimation of buildings in the investigated area, which are discussed in this paper. The method on how to incorporate these stages into a multi-hazard risk assessment framework is also presented. The developed risk assessment framework is then used for the city of Padang that has a considerably high earthquake and tsunami hazard with great exposure to population and infrastructures. The estimated risk obtained in this study is expressed in terms of Pure Risk Premium (PRP) for different building categories commonly found in Padang including unreinforced brick masonry (UBM), confined brick masonry (CBM), reinforced concrete frame with masonry infill (RCI) and steel structures. The earthquake PRP(s) obtained in this study are comparable with the latest insurance rates released by MAIPARK. MAIPARK is an insurance company specialized in earthquake reinsurance, which also provides earthquake statistics and sets a benchmark for earthquake insurance pricing in Indonesia. Tsunami PRP(s) for different building categories in the area are also presented in this paper; however, no comparison can be made due to the unavailability of tsunami insurance premium data for Indonesia. Based on the results, it can be concluded that building risk associated with tsunami in Padang is considerably lower than that of earthquake, due to infrequent occurrence of tsunamis in the area. The earthquake and tsunami risk of buildings in Padang is predicted to be £54.5 million and £30.8 million per annum, respectively.